Advanced microsystems for automotive applications 2011 smart systems for electric, safe and networked mobility - Meyer, Gereon; Valldorf, Jurgen; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
Fundamental transformations are imminent for the automobile today: propulsion technologies are going to shift from combustion engines to electric motors; cars and roads will soon be as safe and convenient as never before; and traffic will flow increasingly efficient. Many of these advancements are due to innovative information and communication technologies, controls and smart systems, both in the vehicle and at its interfaces with the systems for power supply, mobility and data communication. The papers published in this book are selected from the submissions to the 15th International Forum on Advanced Microsystems for Automotive Applications (AMAA 2011) Smart Systems for Electric, Safe and Networked Mobility. They cover components, architectures and smart systems enabling the following functionalities: electric driving, safe cars and roads, and connected vehicles.
Electronic reproduction.
Keywords: Automobiles -- Electronic equipment -- Congresses; Programmable controllers -- Congresses; Microprocessors -- Congresses; Automotive computers -- Congresses; Electronic books